Digital Curation as a Core Competency in Current Learning and Literacy: A Higher Education Perspective - Ungerer, Leona (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
Digital curation may be regarded as a core competency in higher education since it contributes to establishing a sense of metaliteracy (an essential requirement for optimally functioning in a modern media environment) among students. Digital curation is gradually finding its way into higher education curricula aimed at fostering social media literacies. Teachers are urged to blend informal and formal learning and since most people informally use curation in their daily lives for compiling relevant information, it may be fairly easy to adopt digital curation in teaching and learning. Teachers, however, require considerable insight in incorporating various informal digital curation tools in educational practices. The SECTIONS model may assist in guiding decisions around the suitability of digital curation tools for a higher education environment. Including digital literacy training in the professional development of academic staff members may sensitize them to the possibilities that incorporating digital approaches in curricula offer. The Five Cs of Digital Curation framework may guide academic staff members in compiling suitable digital material. There as yet appears not to be a pedagogy that fully acknowledges the various digital curation processes. A pedagogy of abundance, acknowledging that content often is freely available and abundant, may eventually prove relevant in this regard.